Cardiotocography: Obstetric and Neonatal out come - Farkhunda Khursheed, Chandra Madhu Das, Nasreen Jatoi, (Journal of Rawalpindi Medical College, 2009)
Background: To analyze the indications of cardiotocography and to find out its impact on obstetric and neonatal outcome Methods: A total of 210 women, who were more than 36 weeks pregnant and had some clinical indication for Cardio Tocography (CTG) monitoring, were included in the study. CTG was performed in antepartum and intrapartum period and pathological (Non reactive) traces were identified. The outcome was noted in terms of mode of delivery (Vaginal or Cesarean Section), fetal out come (alive, still born neonatal deaths), meconium stained liquor, APGAR score, need for resuscitation and intensive care unit (ICU) admission. To achieve the objective, the results were evaluated in two groups. Group 1 included the women who had reactive pattern of CTG and group 2 included the women who had non reactive pattern of CTG. Results: Reactive pattern was seen in 144 women while 66 women showed non reactive pattern of CTG.In reactive group 62.57% delivered vaginally , while in non-reactive group 27.27% delivered vaginally. In reactive group, 142 (98.61%) babies were born alive and 2(1.38%) were still born. Out of 142 live born babies, there were 4 (2.81%) early neonatal deaths. In non-reactive group 62 (93.93%) babies were born alive and 4 (6.06%) were still born. Among 62 alive born babies in non reactive group, there were 10 (16.12%) early neonatal deaths. Meconium stained liquor was present in 23 (15.97%) babies of reactive group & 18 (27.27%) babies of non reactive group. APGAR score at birth was low (<6) in 44 (30.98%) babies of reactive group and 33 (53.22%) babies of non-reactive group. Resuscitation at birth was required for 44 (30.98%) babies of reactive group and 33 (53.22%) babies of non reactive group. Admission to intensive care unit was required for 24 (16.90%) babies in reactive group and 19 (30.64%) babies in non-reactive group. Conclusion: Fetal compromise is evident in the presence of pathological pattern of CTG . Abnormal CTG necessitates cesarean section . Therefore, adjunctive methods are required to improve the sensitivity and specificity of fetal monitoring if unnecessary interventions are to be avoided.